GRANITIC-GNEISS DERIVED SOILS IN HUMID FOREST-TROPICAL SOUTHWESTEN NIGERIA I: GENESIS AND CLASSIFICATION - AMUSAN, A. A.; ASHAYE, T. I. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
The genesis of granitic-gneiss derived soil in the upland well drained area of humid tropical southwestern Nigeria was studied. The soils have thick (0-20cm dark brown ( (7.5YR - 10YR) coarse sandy loam to sandy clay loam - surface horizon, grading into sandy clay or clay in the subsoils. Presence of sesquioxidic concretions seems to reflect cyclic change of climate. The solum is acidic, low in organic carbon, exchangeable bases and cation exchange capacity. Hydrolytic weathering appears to be the predominant pedogenetic process. The high rainfall, high soil temperature, acidic precipitation and the siliceous parent rock perhaps encouraged this weathering process, resulting in ferrallitic pedogenesis. Free internal drainage as conditioned by topography, geomorphic stability over a considerable geologic period, lessivation. braunification, induration, floral and faunal pedoturbation, mobilization and subsequent immobilization of iron during redox cycles in soils a cyclic change of climate were considered as other dominant pedogenetic processes in the soils. The soils of Iwo series are classified as clayey, kaolinitic, isohyperthermic typic haplustults and Ondo series as clayed kaonilinitic, isohyperthermic, typic kanhaplustults.